Teenage Pregnancy Outcome in Rapti Sub Regional Hospital - Poudel, Sandesh; Rai, Snigdha; Subedi, Kirtipal (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aim: To determine the maternal and perinatal outcome in teenage pregnancies. Methods: A hospital based descriptive cross sectional study conducted from April 2017 to April 2018, among the pregnant women of age group≤19 years, admitted to the labour ward atRapti Sub regional Hospital, Dang. Results: The total of 853 pregnant adolescent women were admitted during the study period, most of which belonged to 19 years of age (38.6%) and were primipara (93.3%) and 42.1% belonged to janjati group. 79.6% had normal delivery, while 14.1% of the cases underwent caesarean section, 5.9% had instrumental delivery and in 0.5% had perineal injury. Anaemia complicated 63% of teenage mothers, more in age group of ≤ 18yrs than in > 18years (61.4%vs 38.6%) and 4.6% had maternal complications, the majority being PPH (2.9%) followed by oligohydraminos, eclampsia, wound infection and vulvar haematoma. Preterm delivery occurred in 15.5% of the cases (≤ 18yrs vs>18yrs being 9.8% vs 5.7%), other neonatal complications included respiratory distress (1.5%), intrauterine growth retardation (4.5%), intrauterine foetal death (0.4%) and very low birth weight (1.2%). Conclusions: Teenage pregnancy has increased risk of adverse pregnancy outcomes leading to various adverse maternal, fetal and neonatal complications. Keywords: outcome, pregnancy, teenage.